Community health worker home visiting in deeply rural South Africa: 12-month outcomes. Issue 11 (2nd November 2021) - Stansert Katzen, Linnea; le Roux, Karl W.; Almirol, Ellen; Hayati Rezvan, Panteha; le Roux, Ingrid M.; Mbewu, Nokwanele; Dippenaar, Elaine; Baker, Venetia; Tomlinson, Mark; Rotheram-Borus, Mary Jane
ABSTRACT: Home visiting by community health workers (CHW) improves child outcomes in efficacy trials, there is however limited evidence of impact evaluating CHW programmes when operating outside of a research project. A CHW programme, previously demonstrated efficacious in a peri-urban township, was evaluated in a deeply rural context in a non-randomised comparative cohort study. Two non-contiguous, rural areas in the Eastern Cape of South Africa of about equal size and density were identified and 1469 mother-infant pairs were recruited over 33 months. In one area, CHWs conducted perinatal home visits (intervention group). Mothers in the comparison group received standard clinic care. Maternal and child outcomes were compared between the groups at one year. Mothers in the intervention group had significantly fewer depressive symptoms than mothers in the comparison group. Children of intervention mothers attained a higher proportion of their developmental milestones, compared to children in the comparison group. There were no other significant differences between mothers and children in the two groups. It is important to establish key parameters for implementing efficacious CHW programmes, especially as the numbers of CHWs are rapidly increased and are becoming critical components of task-shifting strategies of health departments in low and middle income countries (LMIC).